Discovery Learning Model to Improve Critical Thinking Skills of Grade IV Elementary School Students - Yudisthira, Ardhi; Fitri, Sofi Cahya; Izzatika, Amrina; Perdana, Dayu Rika; Apriliyani, Restti (Universitas Islam Negeri Raden Intan Lampung, 2024)
Quality education requires the development of critical thinking skills, especially at the elementary level. These skills are very important for students to be able to analyze information, solve problems, and make the right decisions. One approach that is considered effective in overcoming this problem is the Discovery Learning learning model. The purpose of this study was to determine the effectiveness of the discovery learning model on students' critical thinking skills in grade IV of elementary school. The type of research used was Pre-Experimental Designs with a one group pretest-posttest research design. The subjects of the study consisted of 114 students, with a sample of 28 students selected using purposive sampling techniques. Data were collected through tests and observations. The instrument tests used were instrument validity and reliability tests. The prerequisite tests used were normality tests and homogeneity tests. Data analysis used effectiveness tests. The results showed that the application of the discovery learning model had a positive impact on improving critical thinking skills of grade IV students; there was an increase in learning effectiveness of 40.37%, which was included in the moderate category; and the discovery learning model was able to motivate students to be more active in the learning process.